System Dynamics Model for Improving Salt Quality to Achieve Self-Sufficiency of Industrial Salt - Gustin Ayu Cahyandini; Erma Suryani; Raulia Riski (IPTEK Journal of Proceedings Series, 2020)
Salt is a very important commodity for human life. In addition to consumption, salt is also needed in several industries, including for the Chlor Alkali Plant (CAP) industries, pharmaceutical, and non-CAP industries such as petroleum, salting, and others. The demand for industrial salt in Indonesia continues to increase every year along with the growth and development of industries in Indonesia. However, the salt produced by Indonesian salt farmers is still low in quality and can only meet the needs of consumption salt because they only contain about 94% to 95% NaCl. Therefore, local salt is difficult to be absorbed by with salt-based products industry because its purity level does not meet the industrial standards. As a result, imports of industrial salt will increase because local salt cannot meet the industry needs. This study aims to build a conceptual model in order to improve the quality of salt in Indonesia in order to produce a good quality salt that meet the industrial salt standards and can be absorbed by the industrial sector in Indonesia with system dynamics approach. The results of this study are conceptual models regarding internal and external factors that influence the improvement of salt quality to meet the needs of industrial salt. The model can be used by the government and related parties in developing strategies and policies related to industrial salt cultivation. Further research can be done by developing several scenarios to predict future salt cultivation systems.